Determinants of Misuse of Program Indonesia Pintar (PIP) Funds by Parents and Guardians in Public Elementary Schools: A Case Study of Singkawang City - Kurniasari, Aqida; Zakso, Amrazi; Rustiyarso, Rustiyarso (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This research analyzed factors in the misuse of PIP (Program Indonesia Pintar) funds by parents/guardians of students receiving assistance in its implementation. The research focuses on using PIP funds by parents/guardians of students, school principals, and si-Pintar application operators who are responsible for the school as informants. This research uses a Mixed Methods Research approach which is more dominant in a qualitative approach, starting from a quantitative approach and continuing with a qualitative approach, namely distributing questionnaires which are then analyzed and conducting interviews, observation, and documentation. The results of this research found facts in the field that there was a misuse of PIP funds by recipients who did not comply with the SOP and the misuse of these funds was caused by several factors such as the employment of the student's parents/guardians which had an impact on a low income, the education of the participant's parents/guardians. students which results in a lack of literacy, language limitations, and a lack of socialization from the school, as well as the distribution of PIP funds that are not on target due to invalid data. Apart from that, the 10 schools that are the object of this research have relatively the same socio-cultural life atmosphere even though they are in different areas, namely in terms of economy, work, and education.